Prediction of Service Life Decline of Double Welded Wide Flanges due to Fatigue in Steel Arch Bridge under Excessive Loads - Noor, Rusandi; Asnan, Muhammad Noor (ITB Journal Publisher, LPPM ITB, 2018)
The purpose of this study was to investigate the characteristics of the rate of fatigue fracture propagation in members under maximum force on a steel arch bridge and to identify the fatigue life of those members under excessive loads. The method for bridge fatigue prediction used was numerical S-N curve controlled by cumulative damage rule, fracture critical member, and fatigue fracture determination based on SNI 1729-2015, S-N category. The distribution of stress, strain and life cycle was obtained. The result revealed 1 critical built-up weld beam on the steel arch bridge, specifically double welded wide flange beam TB7. Excessive loads from heavy vehicles, namely trailer types 7C1, 7C2 and 7C3, were simulated. Initial fracturing would occur after 53 years and 5 months of service with an initial crack size of 1.717 mm, leading to a propagation cycle of 45 years, which would cause critical fractures of 10.55 mm after 99 years. Thus, the maximum number of vehicles permitted to enter the bridge, assuming a 5% increase per year, was 13,450 per year for trailer type 7C3 at a planned capacity of 6,984,000 vehicles. This paper illustrates how fatigue life prediction can be a useful guide for the sustainability of bridges and provide a theoretical basis for developing optimized fatigue life of steel arch bridges.